American exceptionalism in inequality and poverty: a (tentative) historical explanation - Lacey, Nicola (Tracing the relationship between inequality, crime, and punishment, 2020)
The United States is a fascinating case study in the complex links between crime, punishment and inequality, standing out as it does in terms of inequality as measured by a number of economic standards; levels of serious violent crime; and rates of imprisonment, penal surveillance and post-conviction disqualifications. This chapter builds on the authors’ previous work arguing that the exceptional rise in violent crime and punishment in the US from the mid-1970s to the early 1990s can be explained by the interaction of four political and economic variables: ‘technological regime change’; ‘varieties of capitalism’ and ‘varieties of welfare state’; types of ‘political system’; and - critically and specifically - the US as a radical outlier in the degree of local democracy. Three further questions implied by the authors’ previous work are asked. First, why did such distinctive patterns of local democracy arise in America? And how is this political structure tied up with the history and politics of race? Second, what did the distinctive historical development of the US political economy in the 19th century imply for the structure of its criminal justice institutions? And third, why did the burden of crime and punishment come to fall so disproportionately on African Americans?